Effect of Si content on the thermoelectric transport properties of Ge-doped higher manganese silicides. (1st July 2017) - Lee, Hwijong; Kim, Gwansik; Lee, Byunghun; Kim, Jeongmin; Choi, Soon-Mok; Lee, Kyu Hyoung; Lee, Wooyoung
Abstract: Polycrystalline bulks of Si-content tuned Ge-doped higher manganese silicides (HMSs) were fabricated to elucidate the effects of Si content on the phase formation behavior and thermoelectric properties. The phase formation and electronic transport characteristics of HMSs were significantly dependent on Si content. Improved power factor was obtained at higher Si contents because of an enhanced Seebeck coefficient due to the increase in density of states effective mass, maintaining electrical conductivity. Furthermore, the lattice thermal conductivity was reduced through Si-content tuning, which suppressed the formation of secondary phases. Thus, a maximum ZT of 0.61 at 823 K was obtained in MnSi1.77 Ge0.027 . Graphical abstract: